Carbon free ultra-fast high temperature sintering of translucent zirconia. (15th March 2022) - Wu, Jinghua; kermani, Milad; Zhu, Danyang; Li, Jiang; Lin, Yong; Hu, Chunfeng; Grasso, Salvatore
Abstract: Ultra-fast High temperature Sintering (UHS) relies on a carbon felt to heat the specimen. As in the case of a graphite furnace, carbon contamination leads to undesired blackening when the UHS temperature exceeds 1800 °C. In this work, we developed a novel UHS configuration based on a tungsten heater energized by a Spark Plasma Sintering machine (UH-SPS). The UH-SPS, with heating rates in the order of 10 4 °C/min, is highly versatile and it allows reproducible and controllable ultrafast firing cycles up to 3000 °C. As proof of concept, we validated the effectiveness of UH-SPS using zirconia as a model system. In comparison with conventional sintering, UH-SPS resulted in a dramatic reduction in the firing time from 10 h to 10-80 s while the specimen maintained a total forward transmittance of 10% at 750 nm. The approach can be generalized to other ceramics degraded by the carbon contamination. Graphical abstract: Image, graphical abstract